Good University Governance Analysis Implementation on Private University in West Java, Indonesia - ., Hanifah (KnE Social Sciences, 2018)
This research aims to understand Good University Governance implementation that includes transparency, accountability, responsibility, independency, and fairness in private universities in the Kopertis Region IV of West Java, which has an ‘A’-accredited study program. The research method used was a descriptive analysis, which describes the variables studied such as transparency, accountability, responsibility, independency, and fairness by using a standard percentage. The research object in this study is Good University Governance within private universities in the Kopertis Region IV of West Java, with an ‘A’-accredited study program in 2015. This research used a sample of five universities. The results of the study show that transparency at the universities and the composition of good university governance in the universities studied was first. Responsibility was in the category of very good (94%), transparency was in the second (82%), accountability was the third (81%), fairness was the fourth (79%) and the fifth was independency (69%). Overall, the qualities were in the good category with an average of 81%. Keywords: Good University Governance, transparency, accountability, responsibility, independency, fairness